Flaubert and Joyce : The Rite of Fiction - Cross, Richard K., 1940- (Book collections on Project MUSE., 1971)
Richard Cross assesses the French writer's impact on his Irish counterpart through a comparison of tone, theme, and technique in their major writings. Juxtaposing passages from their novels, he reveals through textual analysis certain structural and thematic patterns.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.